Creencias y costumbres asociadas al embarazo en la Parroquia Ilumán provincia de Imbabura 2024 - Benavides Cárdenas, Dania Fernanda (2025)
The main objective of this study was to develop an educational guide to contribute to the intervention of beliefs and customs that influence poor adherence in the medical practice of pregnant women in the Iluman parish, Imbabura 2024. For this purpose, the methodology consisted of a quantitative approach, a transversal type with a non experimental model. The analytic-synthetic method was applied to address in a comprehensive and structured way the phenomenon studied. The population was composed of 144 pregnant women from the Iluman parish. The gathering of information was carried out employing a survey and the instrument was the questionnaire. The most relevant results showed that 88% of pregnant women have used traditional practices based on popular beliefs, and 40% have used herbs or infusions to relieve discomfort or pain, thus reflecting the strong cultural influence in their prenatal attention care. Additionally, 62% believed that traditional practices can be more beneficial than medical recommendations, and 54% are aware of the associated risks with these practices. However, only 52% have received adequate information from health professionals. These findings evidenced the need to integrate more appropriately prenatal education and cultural beliefs regarding prenatal health care and make educational intervention an essential aspect within this context.